Analysis of land supporting capacity in development potential for ruminant in Bireuen District - Reza Salima; Ika Rezvani Aprita; Fadlan Hidayat (Serambi Journal of Agricultural Technology, 2020)
The purpose of this research was to determine thepotential land resource for the forage development. The method used is descriptive method by direct observation. The results showed that the overall physiographic conditions of the area in both sites flat to undulating (0-8% slope). All areas are included in the regional development of farm area (Rantau Panyang and Keude Field) included in the moderately suitable (S2) with 2 (two) sub-class of S2wa,fh,nr; and S2wa, fh, lp, nr, in turn, results Actual land suitability evaluation included in the category of moderately suitable land suitability class (S2) with two sub-classes namely S2wa,fh,lp,nr and S2fh, lp, nr.There is a difference between areas in the Rantau Panyang and Keude Lapang good views from the species and botanical composition of the species that dominate in the location of the Rantau Panyang is Cyperus bifax and Imperata cylindrica in the location of Lapang.